2018
DOI: 10.12913/22998624/87042
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Finishing Work on the Geometric Accuracy of the Laser Cut Elements

Abstract: The article presents the results of geometric accuracy studies of the C45 steel elements after laser cutting, and then subjected to finishing work. Burnishing and a combined machining and burnishing were applied as finishing works. Geometric accuracy studies of the elements after laser cutting and after finishing work were conducted in accordance with the PN-EN ISO 9013: 2017-04 standard. It has been noted that the finishing machining enables the improvement of geometric accuracy of the surface after laser cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The C45 steel is defined as a standard material for machinability in the state after normalization annealing [10]. Since the C45 steel was defined as an etalon for steel machining, many authors have analyzed different ways of machining and its influence on the dimension accuracy and resulting machined surface roughness [13][14][15][16][17]. It has been found that the grinding of the C45 steel causes a work hardening of its surface layer without phase transformation [17].…”
Section: Introductionmentioning
confidence: 99%
“…The C45 steel is defined as a standard material for machinability in the state after normalization annealing [10]. Since the C45 steel was defined as an etalon for steel machining, many authors have analyzed different ways of machining and its influence on the dimension accuracy and resulting machined surface roughness [13][14][15][16][17]. It has been found that the grinding of the C45 steel causes a work hardening of its surface layer without phase transformation [17].…”
Section: Introductionmentioning
confidence: 99%